2008
DOI: 10.1080/02652030701779625
|View full text |Cite
|
Sign up to set email alerts
|

Transfer ofFusariummycotoxins and ‘masked’ deoxynivalenol (deoxynivalenol-3-glucoside) from field barley through malt to beer

Abstract: The fate of five Fusarium toxins--deoxynivalenol (DON), sum of 15- and 3-acetyl-deoxynivalenol (ADONs), HT-2 toxin (HT-2) representing the main trichothecenes and zearalenone (ZON) during the malting and brewing processes--was investigated. In addition to these 'free' mycotoxins, the occurrence of deoxynivalenol-3-glucoside (DON-3-Glc) was monitored for the first time in a beer production chain (currently, only DON and ZON are regulated). Two batches of barley, naturally infected and artificially inoculated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
180
4
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(215 citation statements)
references
References 10 publications
20
180
4
11
Order By: Relevance
“…Currently, this technique is being used during baking on an industrial scale to reveal the formation of degradation products of mycotoxins. Moreover, such tracer-fade studies could also be used for elucidation of elevated levels of masked mycotoxins found during malting and brewing [93,94].…”
Section: Metabolomics Approaches To Study Mycotoxin Metabolism In Cermentioning
confidence: 99%
“…Currently, this technique is being used during baking on an industrial scale to reveal the formation of degradation products of mycotoxins. Moreover, such tracer-fade studies could also be used for elucidation of elevated levels of masked mycotoxins found during malting and brewing [93,94].…”
Section: Metabolomics Approaches To Study Mycotoxin Metabolism In Cermentioning
confidence: 99%
“…Furthermore, in these matrices co-occurrence of masked and parent mycotoxins has been previously described (De Boevre et al, 2012a;Berthiller et al, 2009b;Desmarchelier & Seefelder, 2011;He et al, 2010;Kostelanska et al, 2009;Lancova et al, 2008;Vendl et al, 2010). To date however, no risk assessments were performed for masked mycotoxins.…”
Section: Introductionmentioning
confidence: 99%
“…Výměna máčecí vody sice odstraňuje část mykotoxinů, ale při klíčení může docházet opět k jejich nárůstu . Při hvozdění dochází k poklesu obsahu mykotoxinů, ale ne k jejich vymizení (Laitila, 2007;Oliveira, et al ., 2012;Lancová, et al ., 2008) . Plísně a jejich spóry se z infikovaného ječmene a sladu do piva dostat nemohou, nejpozději ve stádiu chmelovaru jsou usmrceny .…”
Section: Monitoring Výskytu Deoxynivalenolu V Pivech Z Obchodní Sítě unclassified
“…Exchange of steeping water removes part of mycotoxins, but they can start to grow again during germination . During kilning, mycotoxins are reduced but not eliminated (Laitila, 2007;Oliveira et al ., 2012;Lancová et al ., 2008) . Fungi and their spores cannot pass from infected barley and malt into beer; they are killed in the phase of wort boiling as the latest .…”
Section: Monitoring Výskytu Deoxynivalenolu V Pivech Z Obchodní Sítě mentioning
confidence: 99%